Revenue decoupling and energy consumption: Empirical evidence from the U.S. electric utilities sector - Victor von Loessl; Heike Wetzel (Philipps-University Marburg, School of Business and Economics, 2019)
Energy efficiency provides a substantial opportunity to tackle increasing greenhouse gas emissions. However, in traditionally regulated energy markets, energy providers maximize their profits by selling electricity or heat as long as their marginal revenue exceeds their marginal costs of production. This so called 'throughput incentive' fundamentally restricts the motivation of utilities to invest in energy efficiency. This paper therefore investigates the relation between the regulatory policy revenue decoupling, that separates utilities' revenue from sales fluctuations, and electricity customers' energy demand and efficiency in the U.S. To address the research question at hand, we follow recent developments in energy demand function modeling and Stochastic Frontier Analysis (SFA) estimation techniques that allow to account for persistent as well as transient efficiency. The estimation results show a signif- icant negative correlation between revenue decoupling and electricity consumption patterns. Furthermore, we find electricity customers have small transient inefficiency. However, results indicate an underlying persistent inefficiency across the entire electric sector.
Keywords: C23; L51; L94; 330; Revenue decoupling; energy efficiency; stochastic frontier analysis; demand frontier function; transient and persistent efficiency